Ethnography of Legal Aid Post-Room: A Review of Equality in Legal Services at the Surabaya Religious Court - Fahmi, Moh. Farih (International Journal of Law Dynamics Review, 2024)
This article explores the opportunities and difficulties that exist for affective control in the Legal Aid Post-Room of the Religious Court (Pengadilan Agama) of Surabaya. Humans and non-human entities coexist in this space, entwined in a relational way to be present together. The ethnographic methodology was selected to get empirical data gathered via five months of observation and interactive discussion. Regarding interpersonal relationships, language use, and the physical space of the Legal Aid Post, the paper contends that Legal Aid workers, informants, and guests are all intertwined. The research findings show ethnographically the atmosphere of the service and reporting process in the Legal Aid Post space as part of the performance in the theater of equality and non-discrimination to demonstrate the sympathetic attitude of Legal Aid officers towards informants. These findings ultimately affirm the presence of emotional atmospheres at certain moments in the Legal Aid Post space, necessitating officers to exhibit creativity. The focus on linguistic expressions to approach feelings and atmospheres in the Legal Aid Post space, in turn, can affect the quality of service. The role of material arrangement, semantic content, and affective experience is utilized to serve the impoverished community in shaping their experiences in seeking justice and the semantic content of what is said